THE INVESTIGATION OF PRODUCTIVE AND RECEPTIVE COMPETENCE IN V+N AND ADJ+N COLLOCATIONS AMONG INDONESIAN EFL LEARNERS - Saudin, Saudin; Sulyaningsih, Iis; Meilinda, Lina (Indonesian Journal of Applied Linguistics, 2017)
The important role of collocation in learnersâ€™ language proficiency has been acknowledged widely. In Systemic Functional Linguistics (SFL), collocation is known as one prominent member of the super-ordinate lexical cohesion, which contributes significantly to the textual coherence, together with grammatical cohesion and structural cohesion (Halliday Hasan, 1985). Collocation is also viewed as the hallmark of truly advanced English learners since the higher the learnersâ€™ proficiency is, the more they tend to use collocation (Bazzaz Samad, 2011; Hsu, 2007; Zhang, 1993). Further, knowledge of collocation is regarded as part of the native speakersâ€™ communicative competence (Bazzaz Samad, 2011); and lack of the knowledge is the most important sign of foreignness among foreign language learners (McArthur, 1992; McCarthy, 1990). Taking the importance of collocation into account, this study is aimed to shed light on Indonesian EFL learnersâ€™ levels of collocational competence. In the study, the collocational competence is restricted to v+n and adj+n of collocation but broken down into productive and receptive competence, about which little work has been done (Henriksen, 2013). For this purpose, 49 second-year students of an English department in a state polytechnic were chosen as the subjects. Two sets of tests (filling in the blanks and multiple-choice) were administered to obtain the data of the subjectsâ€™ levels of productive and receptive competence and to gain information of which type was more problematic for the learners. The test instruments were designed by referring to Brashiâ€™s (2006) test model, and Koyaâ€™s (2003). In the analysis of the data, interpretive-qualitative method was used primarily to obtain broad explanatory information. The data analysis showed that the scores of productive competence were lower than those of receptive competence in both v+n and adj+n collocation. The analysis also revealed that the scores of productive and receptive competence in v+n collocation were higher than those of productive and receptive competence in adj+n collocation. The finding comes as a surprise since it turns out adj+n collocation is more problematic than v+n collocation both productively and receptively. Much research, by contrast, has reported that mistakes in v+n collocation are typical (Al-Zahrani, 1998; Nesselhauf, 2003; Liu, 1999; Sun, 2004). A conclusion has even been drawn that â€œv+n collocation is more difficult than adj+n collocationâ€ (Kuo, 2009, p. 148). Though more studies are needed to support its finding, this research suggests the type of collocation deserve to get more attention from researchers.